PEMIKIRAN SYED MUHAMMAD NAQUIB AL-ATTAS TENTANG ISLAMISASI BAHASA SEBAGAI LANGKAH AWAL ISLAMISASI SAINS - Soleh, A. Khudori (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2010)
Naguib’s Islamization of science is a response to negative impacts of modern science progress (the West) which according to him is not based on Islamic world view. This has an impact on epistemological aspects, so that it can not be used as a method of scientific development in Islamic science. Therefore, there should be reformation of ontology and epistemology to get harmony and usefullness for the development of Islamic sciences. According to Naguib, world view of Islam is monotheism, unity, integration between psyche and physical, spiritual and material, even the spiritual aspect is more important. Based on this, the source of knowledge is not just the material of objects but the meaning of the object, so that knowledge does not fall on positivistic, materialistic and empiric. The method of achieving knowledge is done through the power of observation, rational thought, interpretations of revelation and intuition. The methods are not contradictory but complementary. As the first step of Islamization of science, which change the aspect of metaphysics (world view) and epistemology, according to Naguib, can be started by Islamization of language